2005
DOI: 10.1104/pp.105.066563
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Temperature on Geminivirus-Induced RNA Silencing in Plants

Abstract: Short-interfering RNAs (siRNAs), the molecular markers of posttranscriptional gene silencing (PTGS), are powerful tools that interfere with gene expression and counter virus infection both in plants and animals. Here, we report the effect of temperature on geminivirus-induced gene silencing by quantifying virus-derived siRNAs and by evaluating their distribution along the virus genome for isolates of five species of cassava geminiviruses in cassava (Manihot esculenta, Crantz) and Nicotiana benthamiana. Cassava… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

17
159
2
2

Year Published

2008
2008
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 195 publications
(180 citation statements)
references
References 43 publications
17
159
2
2
Order By: Relevance
“…It is possible that some enzymes in the pathway involved in virus-induced siRNA production might be passivated at extremely low temperatures, while some host factor(s) involved in geminivirus replication, transcription, and/or movement may be less effective at high temperature. Similar results were found previously with lower temperatures inhibiting silencing and higher temperatures eliminating virus replication (Szittya et al, 2003;Chellappan et al, 2005).…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…It is possible that some enzymes in the pathway involved in virus-induced siRNA production might be passivated at extremely low temperatures, while some host factor(s) involved in geminivirus replication, transcription, and/or movement may be less effective at high temperature. Similar results were found previously with lower temperatures inhibiting silencing and higher temperatures eliminating virus replication (Szittya et al, 2003;Chellappan et al, 2005).…”
Section: Discussionsupporting
confidence: 80%
“…In virus-infected plants, high temperatures frequently result in attenuated symptoms and low virus accumulation (Chellappan et al, 2005). By contrast, low temperatures often induce a rapid spread of virus diseases by the control of small interfering RNA (siRNA) generation (Szittya et al, 2003).…”
Section: Discussionmentioning
confidence: 99%
“…Recently, it was shown that viral RNA replication of Raspberry bushy dwarf virus (RBDV), a virus that enters meristematic tissues, was disorganized in leaves and shoot tips of plants growing at a high temperature (38 o C). This was attributed to the enhancement of RNA silencing, the cellular defense mechanism of plants that acts against viral RNA (Wang et al, 2008) and is significantly more active at higher temperatures (Chellappan et al, 2005).…”
Section: Resultsmentioning
confidence: 99%
“…It also remains to be determined whether any of the DRBs play a role in antiviral silencing. One factor that hinders the dissection of the antiviral RNA silencing machinery is that almost all plant viruses encode suppressors of RNA silencing that, depending on the growth conditions of the plants, could partially or completely disable virus-targeted RNA silencing by the plant host (6,(13)(14)(15).In this report, we implicate several more components of the plant RNA silencing machinery in antiviral defense by using mutant viruses devoid of their silencing suppressors. Specifically, we removed the silencing suppressor from our model virus, turnip crinkle virus (TCV) and used the resulting mutant viral RNAs to infect an array of Arabidopsis plants containing mutations in key silencing pathway genes.…”
mentioning
confidence: 94%
“…It also remains to be determined whether any of the DRBs play a role in antiviral silencing. One factor that hinders the dissection of the antiviral RNA silencing machinery is that almost all plant viruses encode suppressors of RNA silencing that, depending on the growth conditions of the plants, could partially or completely disable virus-targeted RNA silencing by the plant host (6,(13)(14)(15).…”
mentioning
confidence: 99%